STEM-Based Hypothetical Learning Trajectory: The Context of Ice Cream Making in Algebraic Multiplication Material - Efriani, Arvin; Arifin, Sujinal; Ananda, Dea (JRPM (Jurnal Review Pembelajaran Matematika), 2026)
This study addresses students' limited understanding of algebraic multiplication and the limited integration of the STEM (Science, Technology, Engineering, and Mathematics) approach in mathematics learning. The aim is to design a STEM-based Hypothetical Learning Trajectory (HLT) for algebraic multiplication and analyze student responses. Using a design research method, the study comprised three stages: preparation, design experiments (pilot and teaching), and retrospective analysis. The participants were seventh-grade students at SMPLTI Indo Global Mandiri Palembang. Data were collected through observation, tests, interviews, and documentation. Results show that STEM-based HLT, grounded in simple ice cream-making, improved students' understanding of algebraic multiplication, their critical thinking, and their engagement and interest. Students also responded positively to contextual learning that integrates STEM components.